Проблема авторського права: чи є ремікс самостійним твором чи порушенням прав оригінального автора - Севрюков, А. О. (ХНУРЕ, 2025)
This thesis is devoted to the legal and moral aspects of remixing. It analyzes the question of whether a remix can be considered an independent work, or whether it is a derivative and requires permission from the original author. It examines the balance between copyright and creative freedom, as well as different approaches to the regulation of remixes in different countries. It also discusses the impact of remixes on the music industry and possible ways to resolve legal disputes in this area.
Keywords: проблема авторського права; ремікс